Amido retrogradado como excipiente de comprimidos para liberação controlada de fármacos: obtenção e caracterização - Recife, Ana Cristina Diniz [UNESP] (2007)
Hydrophilic matrices represent important solid systems for controlled drug delivery intended to oral administration of drugs, because of the relative ease of processing, possibility of incorporating large amounts of drug, and obtaining reproducible release profiles. Resistant starch type 3 (AR3) and pectin (P) are polymers resistant to the action of digestive enzymes and are selectively degraded by colonic microbiota, making them potential candidates for drug delivery systems. In this work, retrograded starch (AR3) was prepared by starch retrogradation by two different methods: Method 1 (M1) - cooling for 8 days at 4° C and Method 2 (M2) - storage for 16 days in alternating temperature cycles (4° C and 30° C, 2 days at each temperature). The physico-chemical properties of the retrograded materials (crystallinity, thermal behavior, swelling and porosity) were evaluated and the results showed structural changes caused by the retrogradation process. Micromeritic properties of these materials (size distribution, shape, density and flow) were also evaluated and showed to be suitable to the compression process. The performance of the materials as tablet excipient intended for controlled drug release was evaluated through the in vitro release of sodium diclofenac in media with different pH values (1.2 and 7.4). The influence of the incorporation of pectin to the systems in controlling the drug release rates was evaluated. The release profiles of all obtained tablets demonstrated effective control of drug release in acid media since tablets prepared with M1 or M2 released from 42 to 49% of drug. Tablets prepared with APR and APM released about 34.5% and 22.8%, respectively. In enteric media, the tablets obtained by M1 or M2 (20 and 40%) showed an increased rate of drug release, so that the t80% occurred at approximately 60 min, while for the tablets obtained with AA this time was of approximately 120 min. The tablets obtained with APR and APM ...